2013
DOI: 10.3390/f4040984
|View full text |Cite
|
Sign up to set email alerts
|

Above-Ground Biomass and Biomass Components Estimation Using LiDAR Data in a Coniferous Forest

Abstract: This study aims to estimate forest above-ground biomass and biomass components in a stand of Picea crassifolia (a coniferous tree) located on Qilian Mountain, western China via low density small-footprint airborne LiDAR data. LiDAR points were first classified into ground points and vegetation points. After, vegetation statistics, including height quantiles, mean height, and fractional cover were calculated. Stepwise multiple regression models were used to develop equations that relate the vegetation statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 35 publications
4
27
2
1
Order By: Relevance
“…In this study, both multivariate linear regression (MLR) model and logistic regression (LR) model were used to account for the relationship of forest ecosystem AGB with the spectral variables selected by stepwise regression analysis [61,62]. MLR is the most widely used method, but many studies have shown that the MLR has several shortcomings such as leading to negative and extremely large estimates.…”
Section: Multivariate Linear Regression (Mlr) and Logistic Regressionmentioning
confidence: 99%
“…In this study, both multivariate linear regression (MLR) model and logistic regression (LR) model were used to account for the relationship of forest ecosystem AGB with the spectral variables selected by stepwise regression analysis [61,62]. MLR is the most widely used method, but many studies have shown that the MLR has several shortcomings such as leading to negative and extremely large estimates.…”
Section: Multivariate Linear Regression (Mlr) and Logistic Regressionmentioning
confidence: 99%
“…Quantifying the amount of forest biomass is necessary for land managers to make informed decisions about forest management and planning [22]. In the current study, a system of compatible individual tree DBH and AGB models was developed using an error-in-variable modeling approach based on airborne LiDAR data.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, a nonlinear least squares regression (NLS) has been used to estimate the parameters in the LiDAR-derived tree variables-DBH or -biomass models [1,11,22]. This method is generally acknowledged as a standard regression technique for modeling the relationship between variables.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, estimates of crown biomass aid in fuel load assessments and fire management strategies (He et al 2013) because it is one of the important input variables in most wildfire models (Saatchi et al 2007). Much of the focus in estimating crown biomass has been in the form of regression models and in the selection of predictor variables rather than in the methods of sample selection.…”
Section: Introductionmentioning
confidence: 99%